When the whales walked : and other incredible evolutionary journeys - Dixon, Dougal (Words & Pictures, an imprint of The Quarto Group, 2018)
Step back in time and discover a world where whales once walked, crocodiles were warm-blooded and snakes had legs! Meet terrifying giant birds, and tiny elephants living on islands in this fascinating creature guide like no other. Learn how whales once walked on four legs before taking to the oceans; how dinosaurs evolved into birds; and how the first cats were small and lived in trees. Featuring a stunning mix of annotated illustrations, illustrated scenes and family trees, evolution is explained here in a captivating and novel style that will make children look at animals in a whole new way.